Research Progress on the Antiosteoarthritic Mechanism of Action of Natural Products. (30th September 2021) - Gao, Mingzhu; Chen, Chun; Zhang, Qiaoyan; Bian, Jun; Qin, Luping; Bao, Leilei
Abstract : Background . Osteoarthritis (OA) is a clinical joint degenerative disease, the pathogenic factors of which include age, obesity, and mechanical injury. Its main pathological features include cartilage loss, narrowing of joint space, and osteophyte formation. At present, there are a variety of treatment methods for OA. Natural products, which are gradually being applied in the treatment of OA, are advantageous as they present with low toxicity and low costs and act on multiple targets. Methods . The terms "natural products, " "osteoarthritis, " and "chondrocytes" were searched in PubMed to screen the related literature in the recent 10 years. Results . We comprehensively introduced 62 published papers on 48 natural products involving 6, 3, 5, 12, 4, and 5 kinds of terpenoids, polysaccharides, polyphenols, flavonoids, alkaloids, and saponins, respectively (and others). Conclusion . The mechanisms of their anti-OA action mainly involve reducing the production of inflammatory factors, reducing oxidative stress, regulating the metabolism of chondrocytes, promoting the proliferation of chondrocytes, or inhibiting chondrocyte apoptosis. This article summarizes the anti-OA activity of natural products in the last 10 years and provides candidate monomers for further study for use in OA treatment.